Pengembangan Aplikasi M-Transaksi Kas Keliling Nasabah LPD Gianyar - Wijaya, Wahyu Septian; Adi Pramartha, Cokorda Rai (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 7 No 4 (2019): JELIKU Volume 7 No 4, Mei 2019, 2019)
The ease of accessing information becomes a very important thing and is a necessity in the digital era now. Currently, collectors of Village Credit Institutions (LPDs) carry out their activities manually, for example recording and accessing information on savings accounts for customers. The development of digital technology has been very rapid, so the collectors want their work to be facilitated by the presence of a digital application that can later help them in activities related to customers and vice versa. The problem that is often faced by collectors is that often the collectors are wrong in recording the savings of their customers. In addition, the loss of books is also another serious problem faced by LPD collectors. And so that the problem can be resolved, a digital application is needed that is expected to facilitate the business processes that have been running on the LPD.